Keamanan Siber dalam Era Digital: Tantangan dan Solusi - Aryapranata, Ariawan; Al Rasyid, Yuliansyah; Agsena, Yogi Priya; Hermanto, Sigit (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2024)
Cybersecurity is becoming a major challenge in today's digital era along with the increasing reliance on information and communication technology. This paper explores various cybersecurity threats such as DDoS attacks, malware, and ransomware and the solutions that can be applied, including the implementation of Vulnerability Assessment and Penetration Testing (VAPT) using tools such as Nmap and Nikto. This research aims to provide insight into the best techniques in cyber threat mitigation and discuss the relevance of VAPT practices in maintaining system integrity.